Law Enforcement against Notaries who Commit Deed Forgery (Case Study of Supreme Court Decision Number 1003/K/PID/2015) - M. Fakhri Rahmat Muzakki*; Yunimar Chaniago; Salman M Noer (Universitas Syiah Kuala, 2023)
This study aims to examine law enforcement against Notaries who forge deeds, find out the basis for judges considerations for imposing criminal penalties in the Supreme Court Decision Number 1003K/PID/2015, and analyze reimbursement of costs, compensation and interest by Notaries who forge deeds. For this reason, the research method used is the Normative Juridical method with a case approach. As for the result of his research, namely: 1) Law enforcement against falsification of authentic deeds by referring to article 264 paragraph (1) of the Criminal code, which carries a maximum prison sentence of eight years. 2) The basis for judges consideration in the Supreme Court Decision Number 1003K/PID/2015 is that the Pekanbaru District Court has wrongly applied the law by releasing the defendant. Thia ia because the notary should change the contents of the deed in front of both parties in accordance with the agreement of both or according to the procedure. 3) Reimbursement of costs, compensation and interest by a Notary for gery of authentic deeds as referred to article 38, article 48, article 49 and article 50 UUJN-P as well as clearly state the amount of compensation, compensation and interest in the petitum of the lawsuit.